Shape morphing technique can accurately predict pelvic bone landmarks - Kuchař, Michal; Henyš, Petr; Rejtar, Pavel; Hájek, Petr (International journal of legal medicine, 2021)
Diffeomorphic shape registration allows for the seamless geometric alignment of shapes. In this study, we demonstrated the use of a registration algorithm to automatically seed anthropological landmarks on the CT images of the pelvis. We found a high correlation between manually and automatically seeded landmarks. The registration algorithm makes it possible to achieve a high degree of automation with the potential to reduce operator errors in the seeding of anthropological landmarks. The results of this study represent a promising step forward in effectively defining the anthropological measures of the human skeleton.
Keywords: senioři; anatomická značka; algoritmy; Algorithms; Tomography, X-Ray Computed; počítačové zpracování obrazu; Middle Aged; mužské pohlaví; Pelvic Bones; Forensic Anthropology; Sex Determination by Skeleton; Non-linear registration; CT data; určení pohlaví podle kostry; ženské pohlaví; Anthropometry; Humans; DSP2 method; pánevní kosti; Anatomic Landmarks; soudní antropologie; lidé středního věku; Image Processing, Computer-Assisted; počítačová rentgenová tomografie; Aged; Female; Geometry segmentation; lidé; Male